تعليم اللغة العربية بإندونيسيا في ضوء العلوم العصبية النفسية - Danial Hilmi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
يتطلب من تعليم اللغة العربية توفير أحوال عقول الدارسين في قبول الدروس وتعبيرها بالقدرة اللغوية. في الواقع أن هناك مشكلات في تحقيقه حيث كانت كفاءتهم الشفهية كالكفاءة الأساسية للغة لا تجري جيدا خاصة في ضوء العلوم العصبية النفسية. هذه الأمور يؤدي إليها إعداد الأهداف والمواد التي لا تراعي احتياجات عقولهم. اختيار طرائق وأساليب تعليمها يفيد الجانب الأيسر من الدماغ كثيرا ولو تقع اللغة فيه، ولكن إذا كان الجانب الأيمن لا يستفاد جيدا فيكون التعليم من متطلبه الاختراعي فيه لا يجري جيدا.The demand of learning Arabic fundamentally requires the optimization of the condition of brain’s learners in receiving and expressing language skills. In reality, problems can be found in the process of implementation in which the speaking competenceas a core language skill cannot be well realized, when particularly inspected through Neuropsychology perspective. This is because the designs of purpose and material do not consider the brain needs of the learners. In addition, selection of instruction methods and strategies tend to reflect the optimization of left brain even though language lies in the left brain. In contrary, if the brain is not well maximized and balanced, then the language learning requiring the creativity embodied in the right brain cannot be well activated too.